2022
DOI: 10.1177/23800844211071111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DHCWs’ Safety Perception on Vaccine Acceptance and Adoption of Risk Mitigation Strategies

Abstract: Objectives: To estimate the association between safety perception on vaccine acceptance and adoptions of risk mitigation strategies among dental health care workers (DHCWs). Methods: A survey was emailed to DHCWs in the New Jersey area from December 2020 to January 2021. Perceived safety from regular SARS-CoV-2 testing of self, coworkers, and patients and its association with vaccine hesitancy and risk mitigation were ascertained. Risk Mitigation Strategy (RiMS) scores were computed from groupings of office me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Across four studies, confidence in reporting test results and testing abilities was high (70%-98%) [ 30 , 34 , 38 , 64 ]. Regular COVIDST by dentists improved perception of safety while treating patients by 49% [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Across four studies, confidence in reporting test results and testing abilities was high (70%-98%) [ 30 , 34 , 38 , 64 ]. Regular COVIDST by dentists improved perception of safety while treating patients by 49% [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…DHCWs to implement such testing in their offices [21]. Furthermore, several challenges exist to routine and comprehensive testing in a dental office setting, including cost, ease of use, and turnaround time.…”
Section: Renderxmentioning
confidence: 99%
“…Dentists have been shown to have an acceptable level of risk awareness [ 7 ]. A study correlating safety perception with vaccine acceptance among dental health care workers revealed that dentists felt less safe with regular SARS-CoV-2 testing and had higher vaccine acceptance, when compared with dental assistants and hygienists [ 8 ].…”
Section: Introductionmentioning
confidence: 99%